PROPOSISI SPIRITUALITAS DALAM REGULASI DIRI BELAJAR SEBAGAI KOPING STRES DALAM PERSPEKTIF PSIKOLOGI PENDIDIKAN ISLAM - Syahidah Rena (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2024)
The ability to know oneself can lead individuals to their goals. On the other hand, self-disregulation will cause emotional and behavioral shocks. To avoid these two forms of interference, the two terms behavioral self-regulation and emotional self-regulation are known. Meanwhile, in correlation to the study of stress coping strategies, these two terms are called